OPTIMASI PENJADWALAN PRODUKSI MENGGUNAKAN METODE CAMPBELL DUDEK SMITH (DI PT. XYZ) - Fathurohman; Muhamad Sayuti; Alexander Lambas T (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2020)
Scheduling is the allocation of limited resources to do a number of jobs. Problems arise when at certain stages of operation some or all of the work requires the same work station. PT XYZ is a service company engaged in electro plating, where the work process is carried out when receiving a request from the customer. The arrival of products from customers who are late and other things will affect the process of working on the products to be plated so that the schedule for sending back products that have been platted is not on schedule while the company does not have inventory. Therefore, a good production machine scheduling optimization will be able to produce good processing time. In addition to knowing the number of machines and jobs as well as the number and sequence of their production processes, research is also carried out by calculating the processing time of each job. Based on the comparison between the best iterations of CDS and the company's FSCS method, it is known that there is a difference in makespan time of 46990 seconds or about 13.05 hours and a flowtime difference of 216380 seconds or about 60.1 hours.